Analysis of the Fairness of Shariah Stock Prices After the Covid-19 Pandemic in 2023 using the Dividend Discount Model Method - Devi Satriawan; Husnul Khatimah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Analysis of the fairness of stock prices is important to determine the right investment decision, ensuring that the risk of loss is minimized for investors. This research was conducted to determine the fair prices of stocks after the Covid-19 pandemic in 2023 in Sharia-compliant companies indexed by the Jakarta Islamic Index (JII). In this research, the Dividend Discount Model (DDM) method was employed to determine the fairness of stock prices. Among the 30 companies listed on the JII index, only 14 operate in the mining sector, and 10 of them have complete financial reports meeting the research criteria. Among these 10 companies, 9 are in an undervalued condition, exhibiting variations in fair prices compared to the closing market price on November 9, 2023. Notably, two stocks, Bukit Asam Tbk (PTBA) and Adaro Energy Indonesia Tbk (ADRO), show fair price differences higher than 10% of the market price. Additionally, seven companies have fair prices greater than the market price by less than 10%, including Vale Indonesia Tbk (INCO), Indocement Tunggal Prakarsa Tbk (INTP), ESSA Industries Indonesia Tbk (ESSA), Aneka Tambang Tbk (ANTM), Indika Energy Tbk (INDY), Barito Pacific Tbk (BRPT), and Semen Indonesia Tbk (SMGR). Conversely, one stock, Perusahaan Gas Negara, Tbk (PGAS), is in an overvalued condition. It is recommended to consider purchasing shares of the nine companies experiencing undervalued conditions.